RNA - Soll, Dieter; Nishimura, Susumu; Moore, Peter, 1939- (Pergamon, 2001)
This publication summarizes the current status of our understanding of RNA, with particular emphasis on the chemistry of this key biological molecule. The various RNAs covered are messenger RNA, ribosomal RNA, transfer RNA and RNA enzymes (ribozymes). The different chapters detail biophysical and chemical methods to investigate RNA structure and function, the synthesis of native and modified RNAs and the latest advances in our understanding of the vast array of biological processes in which RNA is involved.